A Study of the Quality and Availability of Physical Education Infrastructure Senior High School Physical Education Infrastructure: A Case Study of Makassar City - Muhammad Ivan Miftahul Aziz; Sufitriyono Sufitriyono (Musamus Journal of Physical Education and Sport (MJPES), 2024)
The objective of this study is to examine the accessibility and standard of physical education infrastructure facilities in senior high schools and high schools of comparable size in Makassar City. This research aims to ascertain the various elements that exert influence on the accessibility and caliber of infrastructural facilities. Additionally, it seeks to assess the effects of these factors on the educational process and academic performance of students in the field of physical education. Materials and Methods. The Random Sampling technique was employed to select a sample of six high schools in Makassar City for this study, which employed a survey method. Field observations and interviews with pertinent parties, including physical education instructors and students, were employed to accumulate data. An overview of the availability and quality of infrastructure facilities, as well as the identification of extant gaps, will be achieved through data analysis. Results. The analysis of the quality and availability of physical education infrastructure facilities in senior high schools and equivalent in Makassar City reveals inconsistencies between schools. However, the physical education infrastructure facilities in senior high schools and equivalent institutions in Makassar City are generally satisfactory in terms of their quality and availability. This is evidenced by the fact that 77% of the facilities and infrastructure are readily available, while 67% are in excellent condition. All schools in the sample possess a multipurpose field that is suitable for use and in 80% decent condition, similar to a surface that can accommodate a variety of sports. Conclusion. In general, the quality and preservation of the sports facilities in Makassar City high schools require improvement, despite their availability. It is also necessary to enhance the accessibility and variety of facilities to guarantee that all students can participate in an optimal physical education. This study is intended to raise awareness of the quality of physical education, particularly in the areas of facilities and infrastructure, at Makassar City High School. The ultimate goal is to positively influence the health, fitness, and participation of students in various activities. Additional research can investigate the correlation between the quality and availability of physical education infrastructure facilities and other variables, including student sporting accomplishments and student learning outcomes in sports subjects.